2004
DOI: 10.1007/s00702-004-0162-7
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between riluzole and conventional antiepileptic drugs – a comparison of results obtained in the subthreshold method and isobolographic analysis

Abstract: The exact types of pharmacodynamic interactions between riluzole and conventional antiepileptic drugs were evaluated in two available ways, the subthreshold and isobolographic analysis. Maximal electroshock test in mice was used as an animal model for generalized tonic-clonic convulsions. In the first method, riluzole (1.25-2.5 mg/kg) significantly raised the electroconvulsive threshold in mice. The drug administered at its subprotective dose of 0.3125 mg/kg enhanced the antiseizure activity of carbamazepine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Similarly, additivity was reported for the combina-tions of riluzole with carbamazepine, phenytoin, phenobarbital and valproate in the maximal electroshock seizure test in mice [20] . In contrast, the combinations of felbamate with valproate, phenobarbital, clonazepam and ethosuximide in the pentylenetetrazole-induced seizure model exerted antagonistic interactions with isobolographic transformation of data, although the subthreshold method indicated that antiepileptic drugs potentiated their anticonvulsant effects in mice [21] .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Similarly, additivity was reported for the combina-tions of riluzole with carbamazepine, phenytoin, phenobarbital and valproate in the maximal electroshock seizure test in mice [20] . In contrast, the combinations of felbamate with valproate, phenobarbital, clonazepam and ethosuximide in the pentylenetetrazole-induced seizure model exerted antagonistic interactions with isobolographic transformation of data, although the subthreshold method indicated that antiepileptic drugs potentiated their anticonvulsant effects in mice [21] .…”
Section: Discussionmentioning
confidence: 97%
“…0.7, and sub-additivity (antagonism) is evident if the sum of ED 50 fractions is 1 1.3 [18,19] . This experimental procedure has been described in detail in our earlier studies [20][21][22] .…”
Section: Isobolographic Transformationmentioning
confidence: 99%
“…The KCNQ channel (M channel) agonists retigabine, R-L3 and BMS-204352, may be useful for treatment of hypertension, cardiac arrhythmia, epilepsy, and incontinence, while BK channel activators might be used to treat hypertension, stroke, and overactive bladder disorder [19]. The KCNK channel activator riluzole has antiseizure effects in the treatment of epilepsy [20] and may be useful as an antiarrhythmic agent as well. Furthermore, specific channel agonists might be of use in treating several other disorders caused by ion channel dysfunctions, e.g., migraine, episodic ataxia, autosomal dominant deafness, hypokalemic periodic paralysis, and erectile dysfunction [21,22].…”
Section: Activation Of Potassium Channelsmentioning
confidence: 99%
“…Large conductance channel activators could become important in treatment of stroke, hypertension and overactive bladder disorders (Malysz et al, 2004). The activation of KCNK channels by Riluzole exerts significant antiseizure properties (Borowicz et al, 2004). Other possible indications for specific channel openers are reviewed (Cooper and Jan, 1999;Lawson and Dunne, 2001).…”
mentioning
confidence: 99%